Torture-induced hand electrical injury: A case report. (January 2021) - Alqassab, Sufyan; Mathieu, Laurent
Abstract: The authors report an unusual case of hand electrical injury related to torture in a war refugee. The patient was referred for the reconstruction of bilateral hand function several years after being tortured. He presented with severe hand contractures combined with motor and sensory loss. After nonoptimal treatment in the acute period, the reconstruction options were limited by the delayed management. This unique clinical presentation can be explained by repetition of prolonged electrical shocks using a low-voltage current. Highlights: Electrical shock torture is still practiced on war detainees. Repetition of prolonged electrical shocks using a low-voltage current can produce electrical hand injuries. Delayed surgical management is particularly challenging.